Follicular-Phase GnRH Agonist Protocol Is Another Choice for Polycystic Ovary Syndrome Patients With Lower LH/FSH and Lower AMH Levels Without Increasing Severe OHSS Risk - Gao, Rui; Liao, Xin; Huang, Wanrong; Zeng, Rujun; Qin, Lang; Bai, Peng (Frontiers in Endocrinology, 2022)
Purpose: To explore another choice for a controlled ovarian stimulation (COS) protocol that does not increase severe ovarian hyper-stimulation syndrome (OHSS) risk among polycystic ovarian syndrome (PCOS) patients with specific clinical features. Methods: A retrospective study was performed. Two hundred and fifty-nine participants were divided into two groups, Group 1 (fixed GnRH antagonist protocol, n=295) and Group 2 (follicular–phase GnRH agonist protocol, n=69) according to COS protocols. Basic characteristics and laboratory indicators between these two groups were compared. The severe OHSS rate and clinical pregnancy rate were selected as indicators to evaluate the risks and benefits of the two COS protocols. Subgroup analyses for the severe OHSS rate and clinical pregnancy rate were performed based on baseline luteinizing hormone / follicle stimulating hormone (bLH/FSH) and anti–Mullerian hormone (AMH) levels. Results: The severe OHSS rate was statistically higher in Group 2 than in Group 1 (11.6% vs. 3.7%, p=0.008), but the biochemical pregnancy rate and clinical pregnancy rate showed no statistical difference between the groups (71.9% vs. 60.3% and 62.5% vs. 54.3%). In the higher bLH/FSH subgroup (≥ 1.33) and the higher serum AMH levels subgroup (> 3.4 ng/ml), severe OHSS incidence was statistically higher in Group 2 compared to Group 1, but this incidence was lower in the bLH/FSH subgroup (< 1.33) and the subgroup with lower serum AMH levels (≤ 3.4 ng/ml); a difference in severe OHSS risk was not observed. There was no statistical difference between the two groups regarding clinical pregnancy rate in any subgroup. Conclusion: The limited evidence from this study indicates that in PCOS patients with lower bLH/FSH levels (< 1.33) and lower serum AMH levels (≤ 3.4 ng/ml), a follicular-phase GnRH agonist protocol may be another choice that does not increase the risk of severe OHSS